Chronic toxicity of three formulations of neonicotinoid insecticides and their mixture on two daphniid species: Daphnia magna and Ceriodaphnia dubia - Duchet, Claire; Mitchell, Chelsea J; McIntyre, Jenifer K; Stark, John D (Aquatic toxicology (Amsterdam, Netherlands), 2023)
Neonicotinoid insecticides represent nearly a quarter of the global insecticide market and are widely used in agriculture but also for lawn, garden care, and pest control. They are highly water-soluble, persistent in soil, may enter the aquatic compartment via spray drift, runoff, or leaching, and contribute to downstream aquatic toxicity. Although insects appear to be the most sensitive group to neonicotinoids, other groups, such as crustaceans, may also be affected. Furthermore, most studies focus on single-insecticide exposure and very little is known concerning the impact of neonicotinoid mixtures on aquatic invertebrates. The present study was designed to test potential toxicological effects of an environmentally relevant mixture of imidacloprid, clothianidin, and thiamethoxam on populations of Ceriodaphnia dubia and Daphnia magna under controlled conditions. Chronic toxicity tests were conducted in the laboratory, and survival and reproduction were measured for both species under environmentally relevant, 'worst-case' concentrations for each compound separately and in combination as pesticides are often detected as mixtures in aquatic environments. The neonicotinoids did not appear to affect the survival of C. dubia and D. magna. Reproduction of C. dubia was affected by the mixture whereas all three individual insecticides as well as the mixture caused a significant reduction in the reproduction of D. magna. Our results highlight the complexity of pesticide toxicity and show that traditional toxicological approaches such as, acute mortality studies and tests with single compounds can underestimate negative impacts that occur in the environment.
Keywords: thiamethoxam; Mixture; Thiamethoxam; insekticidy; Aquatic invertebrates; Insecticides; Water Pollutants, Chemical; Daphnia; zvířata; Cladocera; Nitro Compounds; neonikotinoidy; dusíkaté sloučeniny; Sublethal effects; chemické látky znečišťující vodu; Neonicotinoids; Animals